Practical wisdom in the living web of the anthropocene - Kim, Hyun-Sook; Yoon, I Sil 19XX-; Joo, Yunsoo; Tran, Mai-Anh Le (International Academy of Practical Theology conference series, 2025)
This book presents essays from transnational and multireligious contexts on how practical theology engages in multidisciplinary analysis of ecological crises and responds by integrating cultural, ethical, and spiritual perspectives into frameworks for sustainable Earth and human community. These peer-reviewed essays were written by participants in the 2023 biennial conference of the International Acade-my of Practical Theology in Seoul, South Korea, under the theme “Practical Wisdom in the Living Web of the Anthropocene.” The concept of the living human web serves as an implicit guiding metaphor, illustrating the intricate and interdependent nature of human connections, and emphasizing the relation-al ties that bind individuals, communities, and broader ecological and social systems. The contributions in this volume demonstrate communal and global effort to address environmental and social crises. Practical theology is framed as a resource for promoting not only analytical depth but also actionable responses rooted in justice, sustainability, and solidarity. Envisioning a practical theology of hope and justice, the essays present a rich tapestry of insights, questions, and aspirations, weaving together diverse strands of practical wisdom. The cover design of this volume was inspired by Jogakbo (조각보), a tradi-tional Korean fabric patchwork technique symbolizing resourcefulness and unity. Just as small fabric pieces form a larger textile, the design reflects the global and communal effort of practical theologians from diverse backgrounds in addressing the environmental crisis and offering hope and justice.